Pengaruh Senam Kreasi terhadap Perkembangan Emosional Anak Usia Dini Kelompok A - Neng Awalia Farida; Risna Nurul Insani; Aeni Latifah; Dede Ridwan; Lidya Nur Illahi; Risna Nurul Insani (Institut Madani Nusantara, 2025)
Emotional development is a fundamental aspect of early childhood that significantly influences children's success in their daily lives and future learning. During early childhood, appropriate stimulation is essential to foster self-confidence, empathy, cooperation, and self-control. One effective approach to promoting these emotional competencies is through enjoyable, meaningful, and child-centered activities, such as creative gymnastics. This study aims to examine the effect of the